Viable Health Games: Elements for Success - Gurkan, Bahadir Gurer (My University, 2016)
The main purpose of this study is to identify the elements of children's health games that have a positive impact on children’s health. The investigation is done by evaluating previous health game studies concentrating on children and five health affairs (such as asthma, cancer, diabetes, nutrition and obesity). In order to do so, firstly the topic of children’s health games is explained through its roots, as it is an interdisciplinary topic pertinent with many other fields. For this reason, the topics regarding the children’s health games as games, video games, children’s gameplay, and serious games along with health, relevant health affairs, and health promotion were covered. Secondly, the meta-study was conducted with the 56 articles on children’s health games. These 56 articles were analyzed with the coding technique defined by Charmaz’s Grounded Theory Method (Charmaz, 2006) for finding out which elements of children’s health games have a positive impact on children’s health promotion. The main result suggests that, although there are 24 different elements found and listed which all positive in their nature, their positive impact is a matter of how they are used or implemented through the consumption cycle of children’s health games and how all these elements interact with each other. In addition to this, a pragmatic proposal is formulated for possibly better or more successful health games. The study concludes with the declaration of the limitations encountered through the research and the recommendations for future research.